Dynamic stability studies of generators in power system using fuzzy logic controller based power system stabilizer - Hasan, Hayfaa Mohammed Hussein (2018)
Excitation systems are affected by low frequency oscillation (LFO)when they are subjected to small perturbations.Damping during the LFOis enhanced via the addition of power system stabilizer (PSS) to the excitation system.This research entails a study on fuzzy logic controller power system stabilizer (FLCPSS) for the purpose of enhancing the stability of a single machine power system.In order to accomplish the stability enhancement,two approaches were used to design fuzzy logic controller (FLC).The first approach includes the use ofgenetic algorithm (GA) to design the PSS.The second approach entails the use of particle swarm optimization (PSO) to design the PSS.The performance of these two approaches is compared with the systemand without PSS.The stabilizing signals were computed using the fuzzy membership functions depending on these variables.The simulations were tested under different operating conditions and also tested with different membership functions.The simulation is implemented using Matlab /Simulink and the results have been found to be quite good and satisfactory.Electro-mechanical oscillations were created in the event of trouble or when there was high power transfer through weak tie-line in the machines of an interrelated power network.This research presents an analysis on the change of speed (Δω), change of angle position (Δδ) and tie-line power flow (Δp).FLC which includes two areas of symmetrical systems are connected via tie-line to identify the performance of the controllers.Simulation results of the fuzzy logic based controller indicate dual inputs of rotor speed deviation and generator’s accelerating power.Two generators have been used to control the arrangement in the tie-line system.The single fuzzy logic controller (S-FLC) has been used as a primary controller and the double fuzzy logic controller(D-FLC) has been used as a secondary controller.Additionally,the system shows a comparison between the two controllers,namely the S-FLC and D-FLC which have been used to achieve the best results.Notably, the double fuzzy controller has been found to have a greater effect on the multi-machine system and it is smoother than the single fuzzy controller as it increased the damping of the speed Δω and rotorangle (degree) Δδ. Its simplicity has made it to be a good controller.In conclusion,much better response can be attained from the S-FLC) if there is careful timing of the scaling factors.